The Relationship between Transformational Leadership and Soft Skills of Village Health Volunteer Leaders in Chachoengsao Province - กราบทิพย์, ญาณันธร; ยืนยง , พันธะกานต์ (Journal of Health Science of Thailand, 2026)
Transformational leadership is the ability to adapt and change in the right direction, enabling teams to ride the waves of change with flexibility and adaptability. Soft skills are a key component in helping leaders deal with obstacles and create an environment conducive to change appropriately. This analytical cross-sectional study aimed to examine the levels and relationships of transformational leadership with soft skills, as well as the impact of transformational leadership on soft skills of the heads of village health volunteers (VHV) in Chachoengsao Province. The sample consisted of 284 heads of VHV clubs at the village, sub-district, district and provincial levels, using Krejcie and Morgan’s sample size calculation formula. The instrument used was a questionnaire on transformational leadership and soft skills of village health volunteer leaders consisted of 3 parts as follows: part (1) a questionnaire on personal characteristics; part (2) opinions on transformational leadership; and part (3) soft skills. The reliability of the whole questionnaire was 0.994. Data were analyzed using descriptive statistics, Pearson’s correlation coefficient, and multiple regression analysis with a stepwise method, with the statistical significance level set at 0.05. The study found that the level of transformational leadership (mean=4.26, SD=0.56) and soft skills (mean=4.18, SD=0.55) were at high levels. Overall, there was a very high positive correlation (r=0.834), with individual consideration (r=0.862) and intellectual stimulation (r=0.815) showing very high positive correlations. Additionally, the predictors of transformational leadership that positively impacted soft skills were individual consideration and intellectual stimulation, predicting 74.8% (R2 = 0.748) of the soft skills of the heads of VHV in Chachoengsao Province, with an error margin of 0.278%. Therefore, continuous enhancement of knowledge in leadership and management will further develop the potential of the heads of VHVs, enabling them to work effectively with sub-district health promoting hospitals, district public health offices, and provincial public health offices.